2020
DOI: 10.18488/journal.61.2020.81.45.56
|View full text |Cite
|
Sign up to set email alerts
|

Instructors Perceptions of EFL Supervisors Classroom Observation Practices at University Level

Abstract: This paper investigated the instructors' perceptions of supervisors' classroom observation practices at Taif University English Language Center (TUELC) in the second semester of the 2018-2019 academic year. The researcher attempted to answer two questions. The first investigated the instructors' perceptions of supervisors' classroom observation practices. The second question investigated the instructors' suggestions for better practices by supervisors. A 4-Likert scale questionnaire was used to gather data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Recently, peer observation has gained significant attention in the higher education sector of Saudi Arabia, especially in contexts similar to our study (see Deraney & AlGhamdi, 2020;Alkhatnai, 2021;Deraney, 2022). This has been evidenced by the growing literature on the topic, including works by Ali (2012), Shousha (2015), andTawalbeh (2020). While peer observation models have been advocated as a valuable tool for evaluating teaching practices, the literature shows that evaluation remains a critical aspect of the process.…”
Section: Peer Observation In the Saudi Contextsupporting
confidence: 69%
See 4 more Smart Citations
“…Recently, peer observation has gained significant attention in the higher education sector of Saudi Arabia, especially in contexts similar to our study (see Deraney & AlGhamdi, 2020;Alkhatnai, 2021;Deraney, 2022). This has been evidenced by the growing literature on the topic, including works by Ali (2012), Shousha (2015), andTawalbeh (2020). While peer observation models have been advocated as a valuable tool for evaluating teaching practices, the literature shows that evaluation remains a critical aspect of the process.…”
Section: Peer Observation In the Saudi Contextsupporting
confidence: 69%
“…In the context of Saudi Arabia, there is a lack of professional training program that focus the attention of language teachers on the value of reflective practice (e.g., Sibahi, 2015). Available studies on peer observation in the context of higher education in Saudi Arabia revealed that the most dominant model of peer observation is the evaluative model (e.g., Shousha, 2015;Tawalbeh, 2020). The following section discusses the developmental model.…”
Section: Collaborativementioning
confidence: 99%
See 3 more Smart Citations